UMRAH ASSISTANCE MANAGEMENT AS A PILGRIM SERVICE STRATEGY AT PT MARCO TOUR & TRAVEL JAKARTA - Maya, Rahendra; Sarbini, Muhammad; Kohar, Ade; Al-Muktazam, Zaid (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This qualitative field study or case study research was conducted at PT Marco Tour & Travel: Umrah & Haji Jakarta, with data collection techniques carried out through direct ovservations and interviews with Umrah pilgrim on various occasions and experience providing Umrah ritual guidance material from 2018 to the present; especially in the 2023 period, which is quite frequent, accompanied by the opportunity to become an unrah guide which is mandated almost every month. Apart from that, this research is also supported by documentary-literature studies, then descriptive-interpretative analysis in carried out. In this research, it was concluded that the satisfaction of umrah pilgrim and smooth and successfull implemetation of their umrah program is through guidance and accompanying umrah rituals. Therefore, the implementation of Umrah ritual guidance must receive good anttention through peofessional and easy Umrah ritual guidance management, especially based on the flow of planning, organizing, actuating, and controlling.